Correction: Necessary and sufficient conditions for the successful three-phase photocatalytic reduction of CO2 by H2O over heterogeneous photocatalysts. Issue 31 (26th July 2018) - Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : Correction for 'Necessary and sufficient conditions for the successful three-phase photocatalytic reduction of CO2 by H2 O over heterogeneous photocatalysts' by Kentaro Teramura et al., Phys. Chem. Chem. Phys., 2018, 20, 8423–8431.